PENGEMBANGAN MEDIA PEMBELAJARAN TRAINING KIT SISTEM KEMUDI SEPEDA MOTOR DI SMK MUHAMMADIYAH 1 BAMBANGLIPURO: Pengembangan Media Pembelajaran Training Kit Sistem Kemudi Sepeda Motor di SMK Muhammadiyah 1 Bambanglipuro. - wahyu muhwanto; samidjo samidjo; nurcholis arifin handoyono (Program Studi Pendidikan Vokasional Teknik Mesin, Universitas Sarjanawiyata Tamansiswa, 2022)
This study aims to determine: (1) the development process; and (2) the feasibility of learning media for motorcycle steering system training kits for students majoring in Motorcycle Business Engineering at SMK Muhammadiyah 1 Bambanglipuro. This research is an R&D (Research and Development) research with the research subjects being students of the TBSM department at SMK Muhammadiyah 1 Bambanglipuro with a total of 18 students and the object of research is the development process and feasibility of the Learning Media Training Kit for Motorcycle Steering System. The data collection technique used a questionnaire. The data analysis technique used the evaluation evaluation criteria analysis to determine the feasibility of the instructional media. The results showed that: (1) The development process went through several stages, namely: (a) Define; (b) Design (Design); (c) Development (Development); (d) Dissemination (Dissemination); and (2) learning media training kit motorcycle steering system suitable for use in the subjects of the TBSM department at SMK Muhammadiyah 1 Bambanglipuro, the feasibility of learning media can be seen from the results of the validation of media experts by 100% with the criteria